Muscarinic receptors regulate intracellular CGMP levels at airway smooth muscle - Alfonzo, Marcelo J.; Gonzálezde Alfonzo, Ramona; Alfonzo González, Marcelo Andrés; Lippo de Bécemberg, Itala A.; Cardillo, Elizabeth (Tribuna del Investigador, 2020)
In this review, we exposed the experimental evidences, related to the cGMP signals, linked to the muscarinic activation of airway smooth muscle (ASM), an essential element in the bronchoconstriction and the remodelling described in asthma and COPD. During this muscarinic activation, two cGMP signals are observed, at 20-s and 60-s, being products of two different muscarinic receptors (mAChRs) associated with two distinctive guanylylcyclases. Thus, the 20-s-cGMP signal involves an M2mAChR inducing a massive and transient α1β1NO-sGC translocation from cytoplasm to plasma membranes. Moreover, the 60-s-cGMP signal is associated with a novel G-protein coupled NPR-GC-B. This nano-machine is regulated by MAChRs, in an opposite way, by an M3mAChR coupled to Gq16 to activate NPR-GC-B and an M2mAChR coupled to Go/1 to inhibit this NPR-GC-B. Moreover, M3mAChRs is desensitizated by dimerization induced by PKG-II phosphorylation. This phosphorylated-M3mAChR binds muscarinic antagonists rather than muscarinic agonists implying receptor desensitization. Recently, we described a novel PDE1A coupled to M2mAChR to finish these cGMP signal transduction cascades. In ASM cells from rats, M2mAChR displays a novel anti-mitogenic effects suggesting that a possible imbalance between these two M2mAChR/M3mAChR signal cascades can contribute to airway hyperreactivity and the abnormal proliferative ASM responses present in asthma and COPD. In asthma experimental model as OVA-sensitized rats, the muscarinic activation of these ASMC exhibited a dysfunction of these cascades involving two M2mAChR/M3mAChR associated with two distinctive cGMP generators, which has been implied in asthma and COPD, opening ways for the development of novel drugs to treat these human diseases.